Management of pathologic fracture of long bones as a complication of acute osteomyelitis: a challenging task for orthopedic surgeons - Ramin Zargarbashi; Fardis Vosoughi; Farhad Shaker; Mozhgan Seifi; Mona Mirbeyk; Amir R. Vafaee (BMC Musculoskeletal Disorders, 2025)
Abstract Purpose The management of pathologic fractures (PF) following osteomyelitis (especially the acute subtype) has not been widely investigated. Therefore, this study aims to assess a stepwise treatment plan for the acute incidence of PF in long bones following pediatric acute Hematogenous osteomyelitis (AHO). Methods This case series was conducted between 2011 and 2023 in a tertiary pediatric center. Patients with fracture incidence within the first 10 days after AHO diagnosis were included. Patients’ characteristics were retrospectively reviewed. Our stepwise treatment plan was as follows: 1. Intravenous antibiotics until ESR<20, then oral to ESR<5 2. Debridement surgery was performed if abscesses were detected. 3. Fracture type determined initial fixation: external fixation or casting. 4. If the union was not obtained, internal fixation (with or without bone graft) was applied 5. Circular external fixation was applied if the union was not obtained or the leg length discrepancy occurred. Results Eight patients (6 boys) with a mean age of 32.1 ± 26.7 months and a follow-up time of 8.64 ± 1.95 years were included. The etiology in all patients was hematological Methicillin-resistant Staphylococcus aureus. Except for one patient who died of septic shock, all other patients (87.5%) reached complete recovery (average length of hospital stay of 19.9 days) and obtained union with an average union time of 14.6 months. A mean of 1.25 surgical procedures, ranging from 0 to 4, were required to obtain union. Conclusion The outcome of the stepwise plan in this study suggests that acute PF following AHO in pediatrics can be managed effectively with favorable clinical and functional outcomes in the mid- and long-term.